One Year in the Pandemic : Results from the High-Frequency Phone Surveys for Refugees in Uganda - Atamanov, Aziz; Beltramo, Theresa; Reese, Benjamin Christopher; Rios Rivera, Laura Abril; Waita, Peter (World Bank, Washington, DC, 2021)
The URHFPS tracks the socioeconomic impacts of the COVID-19 crisis on refugees. The World Bank (WB) in collaboration with the Uganda Bureau of Statistics (UBOS) and the United Nations High Commissioner for Refugees (UNHCR) launched and conducted the URHFPS. The URHFPS tracked the impacts of the COVID-19 pandemic between October 2020 and March 2021. This brief discusses key selected results while providing policy options. Where possible and appropriate, findings are compared to Ugandans by using the national High-Frequency Phone Survey (UHFPS) conducted by UBOS with the support from the World Bank since June 2020.